Chronic inflammation and the hallmarks of aging - Jordan J. Baechle; Nan Chen; Priya Makhijani; Shawn Winer; David Furman; Daniel A. Winer (Molecular Metabolism, 2023)
Background: Recently, the hallmarks of aging were updated to include dysbiosis, disabled macroautophagy, and chronic inflammation. In particular, the low-grade chronic inflammation during aging, without overt infection, is defined as “inflammaging,” which is associated with increased morbidity and mortality in the aging population. Emerging evidence suggests a bidirectional and cyclical relationship between chronic inflammation and the development of age-related conditions, such as cardiovascular diseases, neurodegeneration, cancer, and frailty. How the crosstalk between chronic inflammation and other hallmarks of aging underlies biological mechanisms of aging and age-related disease is thus of particular interest to the current geroscience research. Scope of review: This review integrates the cellular and molecular mechanisms of age-associated chronic inflammation with the other eleven hallmarks of aging. Extra discussion is dedicated to the hallmark of “altered nutrient sensing,” given the scope of Molecular Metabolism. The deregulation of hallmark processes during aging disrupts the delicate balance between pro-inflammatory and anti-inflammatory signaling, leading to a persistent inflammatory state. The resultant chronic inflammation, in turn, further aggravates the dysfunction of each hallmark, thereby driving the progression of aging and age-related diseases. Main conclusions: The crosstalk between chronic inflammation and other hallmarks of aging results in a vicious cycle that exacerbates the decline in cellular functions and promotes aging. Understanding this complex interplay will provide new insights into the mechanisms of aging and the development of potential anti-aging interventions. Given their interconnectedness and ability to accentuate the primary elements of aging, drivers of chronic inflammation may be an ideal target with high translational potential to address the pathological conditions associated with aging.